IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT (TQM) IN IMPROVING DIGITAL LITERACY AND INNOVATIVE ATTITUDE OF SENIOR HIGH SCHOOL TEACHERS - Ine Rahayu Purnamaningsih; Sry Meylaningsih; Uus Kustiana (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT The rapid development of information technology requires teachers to possess digital literacy competencies and innovative attitudes to support effective learning in the digital era. One approach that can support the improvement of these competencies is Total Quality Management (TQM). This study aims to analyze the relationship between TQM implementation and the digital literacy and innovative attitudes of senior high school teachers. The study employed a quantitative approach with a descriptive-correlational design. The population consisted of 40 teachers at SMA YP IPPI Petojo, all of whom were selected as the sample through a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using descriptive and inferential statistics with SPSS version 26. The results showed that the digital literacy and innovative attitude data were normally distributed, with significance values of 0.528 and 0.468 (>0.05), respectively. Digital literacy had a mean score of 45.21 with a standard deviation of 9.484, while innovative attitude had a mean score of 46.15 with a standard deviation of 8.732. The distribution of innovative attitudes was dominated by the score interval of 46–51 (35.0%), indicating a moderate category. These findings suggest that teachers’ digital literacy and innovative attitudes still need further development through the application of TQM principles, including continuous improvement, total involvement of organizational members, and quality-oriented leadership. ABSTRAK Perkembangan teknologi informasi menuntut guru memiliki kompetensi literasi digital dan sikap inovatif untuk mendukung pembelajaran yang efektif di era digital. Salah satu pendekatan yang dapat digunakan untuk mendukung peningkatan kompetensi tersebut adalah Manajemen Mutu Terpadu (Total Quality Management/TQM). Penelitian ini bertujuan menganalisis hubungan implementasi TQM dengan literasi digital dan sikap inovatif guru Sekolah Menengah Atas (SMA). Penelitian menggunakan pendekatan kuantitatif dengan desain deskriptif-korelasional. Populasi penelitian terdiri atas 40 guru SMA YP IPPI Petojo yang seluruhnya dijadikan sampel melalui teknik total sampling. Data dikumpulkan menggunakan kuesioner skala Likert dan dianalisis dengan statistik deskriptif serta inferensial menggunakan SPSS versi 26. Hasil penelitian menunjukkan bahwa data literasi digital dan sikap inovatif berdistribusi normal dengan nilai signifikansi masing-masing sebesar 0,528 dan 0,468 (>0,05). Literasi digital memiliki nilai rata-rata 45,21 dengan standar deviasi 9,484, sedangkan sikap inovatif memiliki nilai rata-rata 46,15 dengan standar deviasi 8,732. Distribusi sikap inovatif didominasi interval skor 46–51 sebesar 35,0%, yang menunjukkan kategori sedang. Temuan ini mengindikasikan bahwa literasi digital dan sikap inovatif guru masih perlu dikembangkan melalui penerapan prinsip TQM, seperti perbaikan berkelanjutan, keterlibatan seluruh anggota organisasi, dan kepemimpinan mutu.